FRI0161 A Phase 1B/2A Study of the Safety, Tolerability, Pharmacokinetics and Pharmacodynamics of XMAB®5871 in Patients with Rheumatoid Arthritis. (9th June 2015) - Jaraczewska-Baumann, M.; Korkosz, M.; Sulyok, G.; Sramek, P.; Rojkovich, B.; Daniluk, S.; Bartalos, J.; Zack, D.J.; Foster, P.
Abstract : Background: XmAb®5871 is a humanized Fc engineered monoclonal antibody (mAb) that binds to the B cell restricted surface antigen CD19 and has enhanced Fc binding to the inhibitory Fcγ receptor IIb (FcγRIIb). Co-ligation of CD19 and FcγRIIb by XmAb5871 has been demonstrated to reversibly down-regulate B cell activity. XmAb5871 is being developed for the treatment of B cell mediated autoimmune disorders. Objectives: The primary objective was to determine the safety, tolerability, PK, PD and immunogenicity profile of XmAb5871 in patients with active RA on stable non-biologic DMARD therapy. A secondary objective (Phase 2a) was to evaluate the effect of XmAb5871 on RA disease response at Day 85 as measured by changes in DAS28-CRP. Methods: This Phase 1b/2a multi-center, randomized, placebo-controlled, double-blinded, clinical study was conducted in patients with active RA despite DMARD therapy. Patients received 6 IV administrations of XmAb5871 or placebo (Pbo) on an every 14 day schedule. In the Phase 1b, 30 RA patients were randomized to Pbo or XmAb5871 in 4 consecutive dose cohorts of 0.3, 1, 3, or 10 mg/kg. After completion of the Phase 1b, 27 patients with active disease were enrolled in the Phase 2a to receive either 10 mg/kg XmAb5871 or Pbo in a 2:1 ratio. Results: A total of 57 patients were enrolled; 40 patients received at least 1 dose of XmAb5871. Complete CD19 receptor occupancy was seen at doses of 1, 3, and 10mg/kg from 1st dose through the completion of dosing. Peripheral B cell count decreased after dosing in all cohorts, with a mean reduction at nadir of ∼50%. The reduction was seen after the 1st dose and did not increase with subsequent doses. XmAb5871 was generally well tolerated, with 2 SAEs in the XmAb5871 group (infusion related reaction, venous thrombosis). The most common treatment related adverse events in the XmAb5871 group were nausea, vomiting or diarrhea that occurred during the 1st infusion in 25% of patients. Two subjects experienced infusion reactions with hypotension (both at 10 mg/kg) and were discontinued. The nature and severity of these infusion reactions were consistent with those reported for other monoclonal antibody therapies. In Phase 2a, there were 15 XmAb5871 treated and 8 Pbo treated patients evaluable for disease activity assessment at Day 85. More subjects treated with XmAb5871 (10 mg/kg) achieved DAS28-CRP low disease or remission at Day 85 than did the Pbo treated subjects (5/15 vs 0/8; 33% vs 0%). In addition, 40% (6/15) of the XmAb5871 treated patients achieved an ACR50 and 20% (3/15) achieved an ACR70 vs 12.5% (1/8) and 0% respectively of the Pbo treated subjects. The mean ACR hybrid score achieved by XmAb5871 treated patients in Part A and B was 42.2, whereas the Pbo patients had a mean of 22.3 at Day 85. Conclusions: The results of this study show that further investigation of XmAb5871 in B cell mediated autoimmune disease is warranted. Disclosure of Interest: M. Jaraczewska-Baumann: None declared, M. Korkosz: None declared, G. Sulyok: None declared, P. Sramek: None declared, B. Rojkovich: None declared, S. Daniluk: None declared, J. Bartalos: None declared, D. Zack Shareholder of: Xencor Inc., Employee of: Xencor Inc., P. Foster Shareholder of: Xencor Inc., Employee of: Xencor Inc.